ANALYSIS OF ATMOSPHERICS, FOOD QUALITY, SERVICE QUALITY, AND PERCEIVED VALUE THAT ARE DIED BY ASICICOMIC SATISFACTION TO BEHAVIORAL INTENTION - Rowlan Takaya (Business and Entrepreneurial Review, 2017)
The problem of this research was to identified the factors that have effects on behavioral intentions such as analsys atmospherics, food quality, and service quality, perceived value, with mediation customer satisfaction.The objectives of this research was people who ever tried Nanny’s Pavillon in South Jakarta. The methodology of this research was the design applies quantitative approach. Data collected by 154 customers of Nanny’s Pavillon. Finding and contribution in this research was provide suggestion for Nanny’s Pavillon to concern about the way to atmospherics, food quality, service quality, perceived value, and customer satisfaction because it has an effect to behavioral intentions for Nanny’s Pavillon.Research Limitation/ implication in this research were this research only for the Nanny’s Pavillon’s customer in South Jakarta, so this result of this research couldn’t be generalization and not applied for all Nanny’s customer in Jakarta